2018
DOI: 10.1055/a-0594-9480
|View full text |Cite
|
Sign up to set email alerts
|

Deutschlandweites Vergiftungsspektrum im Kindes- und Jugendalter

Abstract: Increasing incoming calls from professionals and non-professionals point out the importance of the poison centers. Although intoxications in children and adolescents mainly proceed without or mild symptoms, the relevance of preventive measures especially for children<7 should not be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…It is consistent with the national pattern, in which poisoning by medications was approximately 33% in 2017 (Sistema Nacional de Informações Tóxico-Farmacológicas [SINITOX], 2020). Also, it is in good agreement with previous studies that showed medications as the principal poisoning causative agent in children (Lourenço et al, 2008;Vilaca et al, 2020) (Amorim et al, 2017) (Geith et al, 2018) (Domingos et al, 2016) (Carla Luiza Job Ramos et al, 2010. This prevalence may be attributed to several factors, mainly related to parents or caregivers since children do not have easy access to these substances.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is consistent with the national pattern, in which poisoning by medications was approximately 33% in 2017 (Sistema Nacional de Informações Tóxico-Farmacológicas [SINITOX], 2020). Also, it is in good agreement with previous studies that showed medications as the principal poisoning causative agent in children (Lourenço et al, 2008;Vilaca et al, 2020) (Amorim et al, 2017) (Geith et al, 2018) (Domingos et al, 2016) (Carla Luiza Job Ramos et al, 2010. This prevalence may be attributed to several factors, mainly related to parents or caregivers since children do not have easy access to these substances.…”
Section: Discussionsupporting
confidence: 91%
“…These data vary within poisoning studies and may present significant differences or similar percentages. However, most previous studies have shown a higher males poisoning prevalence (Vilaca et al, 2020) (Geith et al, 2018) (Domingos et al, 2016), as demonstrated in studies conducted in different states.…”
Section: Discussionmentioning
confidence: 84%
“…Während Patienten mit psychiatrischer Vorerkran- [32]. Die Liste der am häufigsten verwendeten Substanzen führten in Übereinstimmung mit der Literatur auch in unserer Studie bei der Gesamtheit der Patienten die Antidepressiva vor den peripheren Analgetika, die bevorzugt von jüngeren Patienten ingestiert werden, und den Neuroleptika an [26,33,34].…”
Section: Vergleich Der Ergebnisse Mit Der Literaturunclassified
“…So gaben Brieger et al kürzlich zu bedenken, dass durch eine ausschließliche Fokussierung auf psychische Erkrankungen andere Faktoren, wie Beziehungskonflikte, Probleme am Arbeitsplatz, finanzielle Schwierigkeiten, Drogenmissbrauch, Wohnungslosigkeit oder somatische Komorbiditäten, unterschätzt und folglich bei der Bereitstellung finanzieller Mittel für präventive Maßnahmen benachteiligt werden könnten [ 32 ]. Die Liste der am häufigsten verwendeten Substanzen führten in Übereinstimmung mit der Literatur auch in unserer Studie bei der Gesamtheit der Patienten die Antidepressiva vor den peripheren Analgetika, die bevorzugt von jüngeren Patienten ingestiert werden, und den Neuroleptika an [ 26 , 33 , 34 ].…”
Section: Vergleich Der Ergebnisse Mit Der Literaturunclassified
“…In Germany, for example, suspected intoxications through plants Note that the absolute ATX-contents span several orders of magnitude and that for many samples individual variants were detected close to the limit of detection. and fungi (excluding tobacco products) were <20 % of total intoxications in children in 2002-2016(Geith et al, 2018 and the share of illnesses thought to be caused by cyanobacteria was 0.25 % of total suspected plant & algae poisonings in 2021 (Stefanie Geith, Poison Emergency Call Centre Munich; pers. Communication).…”
Section: Human Exposure and Risk Assessmentmentioning
confidence: 99%